Biased neurocognitive self-perception in depressive and in healthy persons - Schwert, Christine; Stohrer, Maren; Aschenbrenner, Steffen; Weisbrod, Matthias; Schröder, Annette (Journal of affective disorders, 2018)
Background - Cognitive deficits across several domains and subjective complaints about cognition are prevalent in major depression disorder (MDD). Nevertheless, subjective and objective cognitive functions show no associations. However, research concerning the extent and direction of discrepancy is rare. The present study examined the relationship and discrepancy between subjective and objective cognitive deficits both in patients with MDD and healthy individuals. - Method - Outpatients with MDD (n=102) and a healthy control group (n=88) were assessed with a neuropsychological test battery and completed a questionnaire for the self-assessment of cognitive performance (FLei) concerning the domains of attention, memory, and executive functions. - Results - There were no associations between subjective and objective cognitive deficits in any domain in both the MDD group and the healthy control group. The groups did not differ regarding the extent of the discrepancy between subjective and objective cognition. However, depressed outpatients’ subjective cognitive complaints significantly exceeded their neuropsychological deficits, whereas healthy individuals reported significantly higher subjective cognitive functioning than objectively measured. - Limitations - The cross-sectional study design does not allow for causal conclusions. Due to concerns regarding the suitability of the subjective measure of cognitive deficits used in this study, the findings should be interpreted cautiously. - Conclusions - The current study reveals a discrepancy between subjective and objective cognitive function not only in the MDD group, but also in the control group. Whereas depressed outpatients tend to underestimate their objective cognitive abilities, healthy individuals tend to overestimate them.
Gesehen am 04.09.2019